Linguistic Construction and Cultural Meaning of Sinjang and Semekan: An Anthropological Linguistic Study - Rahmasari, Shafira; Shakti, Zasqia Damai Aulia (HUMANIKA, 2024)
Labuhan Hajad Dalem is an essential ritual in Yogyakarta’s tradition; its primary purpose is to represent prayer and to perform a spiritual cleansing by placing and leaving out some offerings in particular sacred places. Sinjang and Semakan are some of the components of the offering in the form of long fabric to cover a body part. Each Sinjang and Semekan has a different name to illustrate a distinct Javanese cultural value. The naming process is influenced by cultural background, which is Javanese culture, and the name composition is also affected by Javanese linguistic structure. Therefore, this research aims to answer how the naming creation of the offerings, especially the sinjang and semekan using syntactic analysis and an anthropological linguistics approach. Six names of sinjang and fourteen names of semekan are sourced from the official Keraton Ngayogyakarta Hadiningrat website. The names follow a pattern of phrases and clauses, primarily consisting of noun phrases constructed with single nouns, adjectives, or combinations thereof. Additionally, there are clauses formed by noun-verb or noun-verb phrase structures. These names predominantly feature nouns related to various birds and plants, such as perkutut (zebra dove) and mlathi (jasmine), alongside adjectives representing colors like gadhung (green) and pethak (white). Using these colors in the names signifies gratitude, often towards nature and the divine. Furthermore, the selection of nouns reflects the daily life and surroundings of the Yogyakarta community, highlighting the interconnectedness between cultural traditions and local environments.